2020
DOI: 10.1042/bsr20192933
|View full text |Cite
|
Sign up to set email alerts
|

Targeted point mutations of the m6A modification in miR675 using RNA-guided base editing induce cell apoptosis

Abstract: Methylation of the adenine base at the nitrogen 6 position (m6A) is the most common post-transcriptional epigenetic modification of RNA, and it plays a very important role in regulating gene expression. To investigate the role of m6A methylation in the expression of non-coding RNA and miRNA, we used a system of adenine base editors (ABEs). Here, we mutated regions up- and downstream of miRNA 675 m6A modification sites in the H19 locus using HEK293T, L02, MHCC97L, MHCC97H, A549, and SGC-7901 cells. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…METTL3 and FTO have opposing effects on cardiomyocyte apoptosis, likely because of differential regulation of m6A methylation in different target mRNAs. Furthermore, studies have confirmed that targeting point mutations in the m6A modification sites of target transcripts using gene editing technologies can regulate apoptosis ( Hao et al, 2020 ); thus, m6A methylation is a potentially effective means of regulating apoptosis. However, target transcripts that affect apoptosis first need to be identified.…”
Section: M6a Methylation and Cardiovascular Pathophysiologymentioning
confidence: 99%
“…METTL3 and FTO have opposing effects on cardiomyocyte apoptosis, likely because of differential regulation of m6A methylation in different target mRNAs. Furthermore, studies have confirmed that targeting point mutations in the m6A modification sites of target transcripts using gene editing technologies can regulate apoptosis ( Hao et al, 2020 ); thus, m6A methylation is a potentially effective means of regulating apoptosis. However, target transcripts that affect apoptosis first need to be identified.…”
Section: M6a Methylation and Cardiovascular Pathophysiologymentioning
confidence: 99%
“…In order to observe the effects of m6A modifications on miRNA and long non-coding RNA, an adenine base editor system (ABE7.10) was used to induce single site base change. After the targeted mutation of an m6A site (T-A conversion) upstream of miR-675 in the H19 locus in HEK293T cells, miR-675, and H19 expression were observed to be suppressed, resulting in an increase in apoptosis (Hao et al, 2020). It was hypothesized that the reduced expression resulted in an increased presence of p53 protein, thus inducing cell death which indicates the role of m6A in regulating miR675 and H19 expression (Hao et al, 2020), and by extension, cell survival.…”
Section: Dissecting M6a Modifications With Base Editorsmentioning
confidence: 99%
“…After the targeted mutation of an m6A site (T-A conversion) upstream of miR-675 in the H19 locus in HEK293T cells, miR-675, and H19 expression were observed to be suppressed, resulting in an increase in apoptosis (Hao et al, 2020). It was hypothesized that the reduced expression resulted in an increased presence of p53 protein, thus inducing cell death which indicates the role of m6A in regulating miR675 and H19 expression (Hao et al, 2020), and by extension, cell survival. As stated previously, m6A is highly involved in cancer development.…”
Section: Dissecting M6a Modifications With Base Editorsmentioning
confidence: 99%
“…This shows that the methylation modification of miRNA plays an important role in cell. 52 Furthermore, manipulation of miRNA expression or sequence can alter the modification level of m6A by regulating the binding of METTL3 methyltransferase to mRNAs containing miRNA targets. The increase of m6A content promotes the reprogramming of mouse embryonic fibroblasts (MEFs) into pluripotent stem cells.…”
Section: M6a Rna Modificationmentioning
confidence: 99%